Effect of herpes zoster vaccine and antiviral treatment on risk of ischemic stroke. (11th August 2020) - Yang, Quanhe; George, Mary G.; Chang, Anping; Tong, Xin; Merritt, Robert; Hong, Yuling
Abstract : Objective: To determine whether increased risk of acute ischemic stroke (AIS) following herpes zoster (HZ) might be modified by the status of zoster vaccine live (ZVL) vaccination and antiviral treatment following HZ. Methods: We included 87, 405 Medicare fee-for-service beneficiaries aged ≥66 years diagnosed with HZ and AIS from 2008 to 2017. We used a self-controlled case series design to examine the association between HZ and AIS, and estimated incidence rate ratios (IRRs) by comparing incidence of AIS in risk periods vs control periods. To examine effect modification by ZVL and antiviral treatment, beneficiaries were classified into 4 mutually exclusive groups: (1) no vaccination and no antiviral treatment; (2) vaccination only; (3) antiviral treatment only; and (4) both vaccination and antiviral treatment. We tested for interaction to examine changes in IRRs across 4 groups. Results: Among 87, 405 beneficiaries with HZ and AIS, 22.0%, 2.0%, 70.1%, and 5.8% were in groups 1 to 4, respectively. IRRs in 0–14, 15–30, 31–90, and 91–180 days following HZ were 1.89 (95% confidence interval [CI], 1.77–2.02), 1.58 (95% CI, 1.47–1.69), 1.36 (95% CI, 1.31–1.42), and 1.19 (95% CI, 1.15–1.23), respectively. There was no evidence of effect modification by ZVL and antiviral treatment on AIS ( p = 0.067 for interaction). The pattern of association between HZ and risk for AIS was largely consistent across age group, sex, and race. Conclusions: Risk of AIS increased significantly following HZ, and this increased risk was not modified by ZVL and antiviral treatment. Our findings suggest the importance of following recommended HZ vaccination in prevention of HZ and HZ-associated AIS.